Crecimiento de las especies forestales por tipo de bosque y clase diamétrica en la Reserva Nacional Allpahuayo Mishana, Iquitos-Perú, 2021 - Armas Lima, Angelica Solange (2025)
This research was conducted in the Allpahuayo Mishana National Reserve, located in the city of Iquitos, Peru. Natural events such as storms, hurricane winds, etc. produce the opening of the canopy or holes in the forest cover called clearings, in these spaces the growth of forest species in their different dimensions was analyzed. A total of 100 subplots measuring 30 by 15 meters each were assessed using the continuous forest inventory methodology, with a monitoring interval of 10.75 years between successive censuses. The study revealed significant differences in growth patterns based on forest type (primary and secondary) and diameter classes. The secondary forest showed a higher mean annual diameter increment (MAI) of 8.87 mm/year, compared to 4.27 mm/year in the primary forest. When growth was analyzed by diameter classes, a higher growth rate was observed in the lower classes within the secondary forest, a reflection of favorable light conditions caused by canopy openings. However, in the larger diameter classes (≥ 50 cm DAP), individuals in primary forests exhibited greater volume accumulation, reaffirming their ecological significance. These growth patterns underscore the importance of considering both the successional stage of the forest and soil conditions when designing forest management and conservation strategies. Natural gap regeneration emerges as a key opportunity to support ecological restoration while maintaining forest productivity and biodiversity.